The effects of the muscular contraction on the abdominal biomechanics: a numerical investigation. Issue 2 (25th January 2019) - Pavan, Piero G.; Todros, Silvia; Pachera, Paola; Pianigiani, Silvia; Natali, Arturo N.
Abstract: Abdominal wall biomechanics is strongly affected by muscular contraction and intra-abdominal pressure (IAP) which characterize different physiological functions and daily tasks. However, the active muscular behavior is generally not considered in current computational models of the abdominal wall. The aim of this study is to develop a numerical model mimicking muscular activation and IAP. A three dimensional Finite Element model of a healthy abdominal wall is developed detailing the principal abdomen components reconstructed upon anatomical data and medical images. Fascial tissues, aponeuroses and linea alba are modelled as hyperelastic fiber-reinforced materials, while a three-element Hill's model is assumed for muscles. Numerical analyses are performed increasing the IAP up to 100 mmHg and simultaneously activating the muscular structures. The obtained abdominal behavior is compared to a similar model with same IAPs, but passive muscles conditions. Abdomen stiffness and strength are computed in regions in which hernias can potentially occur. A global stiffening of the abdominal wall is found corresponding to a low abdomen deformation and the membrane force on fascial structures is reduced by muscular contraction. Representing active muscular contraction leads to advanced findings, otherwise membrane force results overestimated considering a purely passive behavior for the abdominal wall.